2016
DOI: 10.1016/j.jhin.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and features of hospital-acquired pneumonia: a retrospective cohort study

Abstract: In ward-level hospital practice 'HAP' is an over-used diagnosis that may be inaccurate in 35% of cases when objective radiological criteria are applied. Radiologically confirmed HAP represents a distinct clinical and microbiological phenotype. Potential risk factors were identified that could represent targets for preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 22 publications
3
44
0
2
Order By: Relevance
“…As such, our findings reflect the yield of sputum culture among patients with HAP for whom cultures were successfully obtained. It is not clear why only 29.4% of HAP patients received IDSA guideline-concordant care, but similar rates of culture use are reported elsewhere [13]. While physician decision-making could have contributed to this finding, it is also possible that many sick, hospitalized patients are simply unable to produce sputum for analysis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As such, our findings reflect the yield of sputum culture among patients with HAP for whom cultures were successfully obtained. It is not clear why only 29.4% of HAP patients received IDSA guideline-concordant care, but similar rates of culture use are reported elsewhere [13]. While physician decision-making could have contributed to this finding, it is also possible that many sick, hospitalized patients are simply unable to produce sputum for analysis.…”
Section: Discussionmentioning
confidence: 70%
“…One small single-center study demonstrated positive sputum cultures in 17/35 (48.6%) patients with radiographically confirmed cases of HAP [8], while another demonstrated positive sputum cultures in 57/63 (90.5%) [9]. We aimed to identify the frequency with which sputum cultures positively identify an organism, identify predictors of positive sputum cultures, and characterize the microbiology of sputum cultures in a large cohort of HAP cases.…”
Section: Introductionmentioning
confidence: 99%
“…Case series suggest that both overdiagnosis and underdiagnosis are common. 6,7 Sources of false positives include pulmonary edema, sterile aspiration pneumonitis, pulmonary embolism, lobar collapse, obstructive lung disease exacerbations, vasculitis, cryptogenic organizing pneumonia, sarcoidosis, lung cancer, and others. In addition, the diagnosis of pneumonia itself can encompass a wide range of disease severities.…”
mentioning
confidence: 99%
“…fever, leukocytosis, worsening oxygenation, or purulent tracheal secretions) [6]. This approach has high sensitivity but low specificity for diagnosing VAP, and a normal chest radiograph may not be completely excluding pneumonia [17]. Although chest radiography is widely used despite this limitation, computed tomography (CT) remains the gold standard.…”
Section: Imagingmentioning
confidence: 99%